Supporting victimized children in Iran's legislative criminal policy - Kazemi, Seyyed Sajjad; Sobhani, Neda (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
In today's society, children have a special place and it is no longer the case that the child is considered a family property rather, the child is an individual with his or her own personality and social status and the rights that society has for him / her. But what matters is whether the rights in our society are sufficient for children and just by telling them can it stabilize the child's position within society and save him from any attack? What should be accepted without question is that the answer is no. Because children need special rights and special protections because of their age and physical and intellectual weakness and if there is no executive guarantee to protect them, of course, not only will these rights not be respected, but they will also be violated and children who are more vulnerable than others suffer a lot. What this research specifically focuses on, a comprehensive review of child and adolescent protection law whereas , in accordance with the international obligations our country has committed to and adhered to in compliance with the convention on the rights of the child in 2000, it was approved by the Islamic Consultative Assembly in 2003. In fact, the author's attempt has been to under the pretext of reviewing and evaluating the aforementioned law, evading the existing penal regulations regarding the protection of children and adolescents in the Iranian penal system and thereby evaluate the weaknesses of the aforementioned laws and thus help the legislator to develop and enforce laws protecting certain vulnerable groups such as children.